ELABORATING CRITICAL THINKING SKILLS IN TEFL METHODOLOGY SUBJECT - Yohanes Gatot Sutapa Yuliana (STKIP Persada Khatulistiwa Sintang, 2020)
Elaborating Critical Thinking Skills in TEFL Methodology subject has become one of the 21st century trends, prioritized in the pedagogic process of language courses. Lecturers as facilitators, motivators, boosters, co-learners and inspirational model are the foundation of innovative creativity to adapt and modify comprehensively, and integrate them in their teaching projects contextually; while, the learners themselves play as the active target of learning agents. This modern TEFL Methodology critically makes use of either authentic texts or real texts that are also confronted by the need to approach texts critically. This was revealed in this research, focused on the learners’ activities that enthusiastically engage critical thinking skills in their learning process. It runs actively, innovatively, creatively, dialogically, democratically and in a critical and interactive atmosphere. The importance of applying critical thinking skills in language learning process can empower learners to maximize the objective of TEFL Methodology learning target both oral and written in accordance with their social context. Learners enter in any task using the target language which contains the elements such as identification, investigation, analysis and problem solving then they must think critically. These kinds of communicative task are commonplace for they engage the learners in authentic communication settings. This is impressive and meaningful for the learners. Thus, recommending success in TEFL Methodology subject – as in life - requires effective use of language practically along with some measure of critical thinking.